NEW ANTIVIRAL DRUG COMBINED EFFECT OF THERAPY ARVI IN CHILDREN - I. V. Nikolaeva (Detskie Infekcii (Moskva), 2015)
This article contains a review of Russian and foreign publications with the results of experimental and clinical studies of effectiveness and safety using of a new release active medicine — Ergoferon for the treatment of acute respiratory viral infection (ARVI), including influenza virus. The results of investigation of antiviral activities of Ergoferon and its components in adults are presented in the article, as well as absolutely new data about efficacy and safety of a liquid form Ergoferon in ARVI in children.